A Large Neighbourhood Search Algorithm for Solving Container Loading Problems. (June 2023) - Şafak, Özge; Erdoğan, Güneş
Abstract: This paper presents a Large Neighbourhood Search (LNS) algorithm that finds an effective packing of a set of items into containers. The aim of the LNS algorithm is to provide packing solutions that can be adopted by many logistics companies. The LNS algorithm can handle a set of side constraints such as orientation, stacking, and separation as well as weight limit, loading priorities, and stability to address the issues arising for loading the items. The packing solution is also visualised and animated using an Excel workbook to help the workers for loading of the items. Finally, the authors present a comparison between the performance of the LNS algorithm and the state-of-the-art algorithms from the literature based on benchmark data sets. The results demonstrate the quality of the solutions achieved by the LNS algorithm. Highlights: A Large Neighbourhood Search algorithm for the Container Loading Problem is studied. The algorithm returns comparable results to the state-of-the-art heuristics. The algorithm is implemented into an open-source Excel spreadsheet. The spreadsheet has a visual interface and is publicly available.